PENGARUH STRATEGI DIFERENSIASI TERHADAP LOYALITAS KONSUMEN BISNIS JASA PENGIRIMAN PT. POS INDONESIA (Persero) PEKANBARU - Muntaha, Atika Sidratul; ", Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research aims to determine the effect of product differentiation, service differentiation, and image differentiation to the consumer loyalty shipping service business PT. Pos Indonesia (Persero) Pekanbaru partially and simultaneously. This research uses sub variable that is Product Differentiation, Service Differentiation, and Image Diferensiasi. This research was conducted at PT. Pos Indonesia (Persero) Pekanbaru which is located at Jalan Jendral Sudirman no. 229 Pekanbaru. In this research the methodology used is descriptive and quantitative with SPSS program, where the sample in this research is consumer of PT. Pos Indonesia (Persero) Pekanbaru as many as 100 respondents. To determine the sample using Slovin formula, sampling method with purposive sampling. Data collection techniques through questionnaires.From the data analysis covering validity test, reliability test, classical assumption test, simple linear analysis, multiple linear analysis, determination analysis, and significance test with t test (partial), and f (simultaneous) test. The result of this research shows that the result of test of first t test hypothesis, product differentiation to consumer loyalty is t arithmetic (12,972) > t table (1,6608) meaning product differentiation have significant effect to consumer’s loyalty. Second, service differentiation to consumer loyalty is t arithmetic (8,920) > t table (1,6608) meaning service differentiation have a significant effect to consumer loyalty. Third, image differentiation to consumer loyalty is t arithmetic (12,525) > t table (1,6608) meaning image differentiation have significant effect to consumer loyalty. F product differentiation test, service differentiation, and image differentiation to consumer loyalty are F arithmetic (80,972) > F table (2,70). This means product differentiation, service differentiation, and image differentiation simultaneously significantly influence consumer’s loyalty.Keywords: Product Differentiation, Service Differentiation, Image DifferentiationConsumer loyalty